Menakar Dampak Literasi Keuangan Syariah, Islamic Branding Terhadap Minat Menjadi Nasabah - Srisulistiowati, Dwi Budi; Syarifudin; Erasma; Widyaswati, Rahmatya; Musdirwan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The banking world currently dominates the economic growth of a country, both in developed and developing countries. The increasing industrial growth also occurs in the Indonesian Islamic banking industry. The purpose of the study was to see the effect of Islamic financial literacy, Islamic branding on the interest in becoming a customer of Bank Mega Syariah KC Mataram. This research uses a quantitative method with regression analysis. The sampling technique in this study is using purposive sampling. The sample used as the object of research is customers who have registered at Bank Syariah Indonesia, so that 55 respondents were obtained. The data were analyzed using multiple linear regression analysis with the SPSS 25 program. Based on the results of the analysis, Islamic financial literacy, Islamic branding partially influenced the interest in becoming a customer at Bank Mega Syariah KC Mataram. The results of the study obtained an R2 value of 0.876 (87.6%), this means that the interest in becoming a customer is influenced by Islamic financial literacy, Islamic branding by 87.6%, the remaining 12.4% is influenced by other factors outside this study.